Wholesale Electricity Market: Agents and Organization Models - Lozano, Jean (2018)
This article presents a review of models that served as the basis for the design of competitive electricity markets currently in operation in most of the world. First, we explains the main characteristics of electricity that differentiate it from any other product that can be marketed in an organized market. Then, we describe the agents that can participate in the electricity market and we present a market classification according to the degree of competition within the current context of liberalization. Finally, we made an analysis of the models of organization and operation of electricity markets with competition in the wholesale market.